2019
DOI: 10.9734/ijpss/2019/v27i330078
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Mungbeans (Vigna radiata (L) Willczek) in Soil Amended with Oil Palm Bunch Ash and Poultry Manure in Humid Tropical Environment of South Eastern Nigeria

Abstract: Aim: A study was conducted to evaluate supplementary effects of oil palm bunch ash (OPBA) and poultry manure (PM) on the growth and yield performance of mungbeans. Study Design:  The study used a 3 x 3 factorial experiment laid out in randomized complete block design with three replications. Place and Duration of Study: The experiment was carried out at the University of Calabar Teaching and Research farm, Calabar, Nigeria during the 2014 and 2015 cropping seasons respectively Methodology: Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The soil was also observed to be strongly acidic in soil reaction with a pH of 5.4, having low exchangeable cations (Ca 2+ , Mg 2+ , and K + ), OC, and total nitrogen. The previous studies [5,6,27] also reported that "essential nutrients such as total N, organic C, and exchangeable cations in coastal plain soils are mostly low, and the low status of these nutrients in the experimental soil is an indication of low fertility." Thus, an additional supply of nutrients through biochar and PM to improve the growth and yield of cucumber was necessary.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The soil was also observed to be strongly acidic in soil reaction with a pH of 5.4, having low exchangeable cations (Ca 2+ , Mg 2+ , and K + ), OC, and total nitrogen. The previous studies [5,6,27] also reported that "essential nutrients such as total N, organic C, and exchangeable cations in coastal plain soils are mostly low, and the low status of these nutrients in the experimental soil is an indication of low fertility." Thus, an additional supply of nutrients through biochar and PM to improve the growth and yield of cucumber was necessary.…”
Section: Discussionmentioning
confidence: 93%
“…Whereas several research studies including Uko et al [5] have reported poultry manure (PM) to possess high nutrient contents, most especially total nitrogen, and have been used as organic fertilizer for soil amendment for several decades now [18]; nevertheless, its excessive direct application to the soil has many environmental consequences including but not limited to ammonia volatilization, groundwater contamination, greenhouse gas emission, and emission of offensive odors [5,19,20]. Similarly, the application of biochar alone may be limited in supplying all the essential plant nutrients required for crop growth due to its low nutrient contents and recalcitrance to biodegradation [21].…”
Section: Introductionmentioning
confidence: 99%